2005
DOI: 10.1097/00042737-200511000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Safe use of pegylated interferon/ribavirin in hepatitis C virus cirrhotic patients with hypersplenism after partial splenic embolization

Abstract: PSE allowed the safe use of peg-IFN plus ribavirin in HCV cirrhotic patients with severe cytopenias who otherwise would never have been treated. The rate of SVR was 38%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
51
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 34 publications
3
51
0
Order By: Relevance
“…All 30 patients were able to receive therapy with pegylated interferon and ribavirin following a PSE-related increase in their platelet counts. A handful of other studies have demonstrated similar findings over the past decade [21][22][23] . Similar to the use of PSE to improve platelet counts prior to antiviral therapy in patients with hepatitis C, PSE has been used to increase hematologic indices to facilitate treatment of hepatocellular carcinoma.…”
Section: Complications Of Psesupporting
confidence: 64%
“…All 30 patients were able to receive therapy with pegylated interferon and ribavirin following a PSE-related increase in their platelet counts. A handful of other studies have demonstrated similar findings over the past decade [21][22][23] . Similar to the use of PSE to improve platelet counts prior to antiviral therapy in patients with hepatitis C, PSE has been used to increase hematologic indices to facilitate treatment of hepatocellular carcinoma.…”
Section: Complications Of Psesupporting
confidence: 64%
“…To date, several papers on the efficacy of PSE prior to starting interferon therapy have been already reported (12)(13)(14)(15)(16). First, Moreno et al (12,13) reported the usefulness of PSE prior to starting the combined therapy with peginterferon and ribavirin in HCV cirrhotic patients with thrombocytopenia; however, their reports were one-arm studies and did not have a non-PSE group.…”
Section: Discussionmentioning
confidence: 99%
“…To date, several papers on the efficacy of PSE prior to starting interferon therapy have been already reported (12)(13)(14)(15)(16). First, Moreno et al (12,13) reported the usefulness of PSE prior to starting the combined therapy with peginterferon and ribavirin in HCV cirrhotic patients with thrombocytopenia; however, their reports were one-arm studies and did not have a non-PSE group. Furthermore, although the currently recommended therapy of chronic HCV infection is the combination of peginterferon and ribavirin (5), the study population of other 2 reports mainly consisted of patients treated with conventional interferon or consensus interferon (14,15).…”
Section: Discussionmentioning
confidence: 99%
“…Hypersplenism can be corrected by laparoscopic splenectomy or partial splenic embolization. 11 But these procedures are associated with morbidity such as portal vein thrombosis, infection, or worsening of liver function. Besides, the rise of platelets after partial splenic embolization may only be shortlived.…”
Section: Strategies To Boost Platelet Count In Hepatitis C Patientsmentioning
confidence: 99%